Determinates of muscle precursor cell therapy efficacy in a nonhuman primate model of intrinsic urinary sphincter deficiency. Issue 1 (December 2017) - Williams, James; Dean, Ashley; Lankford, Shannon; Criswell, Tracy; Badlani, Gopal; Andersson, Karl-Erik
Abstract Background Cell therapy for intrinsic urinary sphincter deficiency (ISD) in women has been moderately effective, and improvements are needed. To improve treatment efficacy, it is important to better understand determinates of cell efficacy in the different patient cohorts. We have reported that in nonhuman primates the chronicity of ISD may affect cell efficacy, but additional factors (age, psychosocial stress, hormone status, body weight) can be associated with many disease/treatment outcomes in women – and these factors are the focus of this study. Methods Adult female cynomolgus monkeys were divided into groups: (1) younger (n = 10, 5–8 years of age) versus older (n = 10, 13–18 years of age); (2) age-matched/socially subordinate (n = 15) versus socially dominant (n = 15); and (3) age-matched lower body weight (n = 6) versus higher body weight (n = 6). Autologous skeletal muscle precursor cells (skMPCs, 5 million) were injected into the urinary sphincter 6 weeks after a surgically induced ISD procedure. Resting and pudendal nerve-stimulated maximal urethral pressures (MUP) were measured before, and 3 and 6 months post-skMPC treatment and urinary sphincter muscle/collagen content within the sphincter complex was measured by quantitative histology 6 months posttreatment. Results Efficacy of skMPCs on MUP and sphincter muscle/collagen ratios are affected by age (average 40% reduction in efficacy, p < 0.05 vs. younger NHPs), social stress (average 30% reduction in efficacy, p < 0.05 vs. socially dominant) and body weight/fasting glucose concentrations (average 35% reduction in efficacy, p < 0.05 vs. lower body weight). Conclusion Multiple factors (age, stress-induced dysmenorrhea, and body weight) affect the efficacy of cell therapy to restore structure and function in the urinary sphincter complex in NHPs with ISD. Consideration of, and alternatives for, these patient cohorts should be considered.